Avaliação da incidência de deiscência profunda da aponeurose no pós-operatório de colectomias eletivas realizadas no Hospital das Clínicas de Botucatu - Beltrami, Marco Aurélio Leão [UNESP] (2024)
Introduction: Aponeurosis dehiscence (AD) is a significant surgical complication that can result in enduring structural damage and death. There are several established scores in the literature that incorporate preoperative, intraoperative and postoperative variables to classify the risk of aponeurotic dehiscence. Objectives: Our study aimed to determine the prevalence of aponeurotic dehiscence in pacients undergoing colectomy and to evaluate the proportion of patients who benefit from prophylactic mesh use based on the Vidal score. Method: A descriptive, retrospective, cross-sectional study was carried out on patients who underwent colectomy with an infraumbilical midline incision at a hospital of São Paulo state between 1 January 1st 2020 and July 31st 2022. Participants were divided into two groups based on their main outcome, identifying those who developed an incisional hernia and those who did not, and calculating the frequency of these events. All participants in the sample were assessed according to AD risk using the Vidal Score to determine those who necessitated a prophylactic mesh. Outcomes: 152 surgeries were performed during the period, 39 of which were excluded because they did not meet the study inclusion criteria, resulting in a sample of 113 patients.. A total of 152 patients underwent surgery during the study period. The evaluated cohort consisted of 59 female participants, accounting for 52.2% of the sample, with an age range of 19 to 85 years. Among them, the incidence of hernia was observed in 53 cases, representing 46.9% of the sample. 15 OF these cases were detected by physical examination and 37 were diagnosed by imaging techniques. All patients underwent elective surgery, with 94 individuals (83.1%) undergoing surgery for malignant neoplasms. During the assessment of prophylactic mesh usage, 96 (84.95%) patients displayed an indication according to the Vidal score. Among them, 50 (44.2%) were diagnosed with incisional hernia. Intraoperatively, the suture type used for aponeurosis closure was evalueted. Polydioxanone was the most commonly used suture, being preferred in 80 (70.7%) cases, followed by polypropylene, used in only 15 (13.2%) cases. Conclusion: The incidence of aponeurotic dehiscence remains high, especially in high-risk groups such as cancer patients. Therefore, there is a potential benefit with the use of prophylactic mesh in this population.